REDEFINING ALZHEIMER’S DISEASE THROUGH MODERN BIOTECHNOLOGY; FROM MOLECULAR PATHOGENESIS TO INNOVATIVE THERAPEUTICS AND DIAGNOSTIC FRONTIERS (Journal of Medical & Health Sciences Review, 2025)
This article tells us how modern biotechnology and AI are redefining Alzheimer’s disease through early detection, advanced biomarkers, and innovative treatments like lecanemab. It highlights global impact, behavioral aspects, and the role of lifestyle and technology in improving outcomes. Genetic and molecular mutations lead to onset of AD. Mutations in APP, PSEN1, PSEN2, along with risk factor such as APOE  ε4 that increase the production of amyloid-β₄₂ and impaired amyloid clearance that later form neurotoxic plaques. These process also influence tau pathology, synaptic failure and neurodegenerative characteristic of alzheimer disease. Biomarkers have played a crucial role in the pre determination of Alzheimer's disease and have used to make precautionary measures. Imaging and biomarkers have been found to enable prevention measures to be taken early, and treatment is done with ChEIs, memantine, and anti-amyloid antibodies such as lecanemab and donanemab. New treatments are aimed at amyloid, tau, and inflammation, and genes, and stem cell and non-pharmacological interventions. New biotechnologies like gene editing, stem cells, nanotech, and AI are helping scientists better understand and treat Alzheimer’s disease. These modern tools make it possible to find the disease early and give more effective, personalized treatments.